Mechanistic Investigation of Lysine-Targeted Covalent Inhibition of PI3K delta via ONIOM QM:QM Computations - ERDEM, SAFİYE; FINDIK, VOLKAN (My University, 2022)
Phosphoinositide 3-kinase (PI3K) enzymes are important drug targets, especially in oncology, and several inhibitors are currently under investigation in clinical trials for the treatment of lymphocytic leukemia, follicular lymphoma, breast, thyroid, colorectal, and lung cancer. Targeted covalent inhibitors hold significant promise for drug discovery research especially for kinases. Targeting the lysine residues attracts attention as a new strategy in designing targeted covalent inhibitors, since the lysine residue provides several advantages over the traditional cysteine residue. Recently, new highly selective covalent inhibitors of PI3K delta with activated ester warheads, targeting the conserved Lys779 residue, were reported. Based on the observed kinetics, a covalent inhibition mechanism was proposed, but the atomistic details of the reaction are still not understood. Therefore, in the present work, we have conducted quantum chemical ONIOM M06-2X/6-31+G(d,p):PM6 calculations on the active site cluster structure of PI3K delta to elucidate the microscopic details of the mechanism of the aminolysis reaction between Lys779 and the ester inhibitors. Our calculations clearly discriminate the noncovalent methyl ester inhibitor and the covalent inhibitors with activated phenolic esters. For the representative p-NO2, p-F, p-H, and p-OCH3 phenolic esters, the Gibbs free energy profiles of alternative mechanistic paths through either Asp782 or Asp911 demonstrate the modulatory role of active site aspartate residues. The most plausible path alters depending on the electron-withdrawing/donating nature of the psubstituted phenolate leaving group. Inhibitors with sufficiently strong electron-withdrawing group prefer direct dissociation of the leaving group from the tetrahedral zwitterion intermediate, while the ones with electron-donating group favor the formation of a neutral tetrahedral intermediate prior to the dissociation. The relative Gibbs free energy barriers of p-NO2 < p- F < p-H < p-OCH3 substituted phenyl esters display the same qualitative trend as the experimentally measured k(inact)/K-1 values. Our results provide in depth insight into the mechanism, which can pave the way for optimizing the inhibitor efficiency.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Bilgisayar Grafiği; Yaşam Bilimleri; Kimya; Biyokimya; Alkoloidler; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Computer Sciences; Information Security and Reliability; Computer Graphics; Life Sciences; Chemistry; Biochemistry; Alcaloides; Health Sciences; Natural Sciences; Engineering and Technology; KİMYA, TIP; Temel Bilimler (SCI); KİMYA, MULTİDİSİPLİNER; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); CHEMISTRY, MEDICINAL; CHEMISTRY; Natural Sciences (SCI); Engineering, Computing & Technology (ENG); Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yer Bilimlerinde Bilgisayarlar; Bilgi sistemi; Bilgisayar Bilimi Uygulamaları; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Computers in Earth Sciences; Information Systems; Computer Science Applications; Computer Graphics and Computer-Aided Design; Computer Science (miscellaneous); General Computer Science; Chemistry (miscellaneous); General Chemistry; Physical Sciences